How are you, really? : A dialogue about depression - Chua, Cheryl Xin Ting (Nanyang Technological University, 2021)
How Are You, Really? is a communication campaign that aims to empower youths aged 19 to 24 in Singapore with the ability to provide functional support to close others with depression. Depression is the most common mental health condition in Singapore, with 1 in 16 people having suffered from it once in their lifetime, and numbers set to rise in light of the COVID-19 pandemic. Recognising the importance of peer support in accelerating the recovery process for depression, the campaign sought to equip youths with the knowledge and skills to provide functional support to their close others, enabling them to realise that having conversations about depression is within their abilities, thereby normalising such conversations in Singapore. Guided by the Social Cognitive Theory, the campaign employed a multi-pronged approach comprising a social media strategy, podcast series and on-ground event, to enable youths to go beyond the superficial and reach deeper by being empowered to help close others with depression. The campaign successfully promoted the enhancement of knowledge about depression and functional support, which empowered more youths to engage in deeper conversations with close others about depression. The 13-week-long campaign also gained significant digital traction, yielding $106,629 in PR value. This paper will present a comprehensive analysis of the importance of a holistic support system by close others for youths with depression in Singapore, followed by the campaign strategies implemented from development to evaluation. Subsequently, the paper will also detail limitations, recommendations and future plans for the campaign’s sustainability.